PENGARUH PENERAPAN MODEL INKUIRI DAN DISCOVERY TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM DI MTs AS’ADIYAH PUTRI II SENGKANG - ., Samsidar; Ondeng, Syarifuddin; Ismail, Ilyas (Inspiratif Pendidikan, 2019)
The purpose of this study is to describe and test the effect of the application of inquiry and discovery models on the learning outcomes of Islamic Cultural History in MTs. As'adiyah Putri 2 Sengkang. This type of research is an ex-post facto research with a quantitative approach. The population in this study were students in MTs As'adiyah Putri 2 Sengkang. Sampling was done by random sampling of 66 students. The results of the study found the effect of applying the inquiry model of 21.4% and discoveri of 5.1% on the SKI learning outcomes. The effect of inquiry and discovery models on student learning outcomes in Islamic Cultural History subjects at MTs. As'adiyah Putri 2 Sengkang by 21.5%. while the remaining 78.5 percent is influenced by other factors.